PREVALENCIA, SEVERIDAD Y NECESIDAD DE TRATAMIENTO DE LA ENFERMEDAD PERIODONTAL EN PERSONAL DEL BATALLÓN DE ARTILLERÍA DE DEFENSA AÉREA NO. 2 NUEVA GRANADA (2013)
Objective: to assess the prevalence, severity and periodontal treatment needs in soldiers from the Air Defense Artillery Branch # 2 Nueva Granada in the city of Barrancabermeja.Methods: a cross sectional study was done. A tactical unit of the Nueva Granada Battalion was considered as the universe. A nonprobability convenience sampling was conducted and 120 soldiers were included. To determine the status of periodontal health a periodontal chart was proposed by the World Health Organization was used, also the Community Periodontal Index of Treatment Needs was measured. Frequencies and percentages for categorical variables and measures of central tendency and dispersion for quantitative variables were calculated. The Chi2 test was performed with a value of p < 0.05 considered statistically significant.Results: the prevalence of periodontal disease found was 100%. No statistically significant difference between periodontal disease and the analyzed variables (age, socioeconomic status, educational level) were observed. The severity of the disease was 74.8% for the mild, moderate and severe levels. The Community Periodontal Index of Treatment Need was representative in criterion 3 (pockets 4mm – 5mm) with 34.6% and the need for treatment required was Oral hygiene instructions and root surface debridement.Conclusions: the prevalence, severity and need for treatment observed were high. All the soldier evaluated from the Granada Battalion required treatment. It is necessary to direct efforts to improve the conditions of oral and periodontal health in this population.